ACCURACY OF OPERATING PATTERNS IN LANAL TAREMPA IN THE FACE OF REGIONAL VIOLATION RATES WITH DOUBLE HOLT WINTERS EXPONENTIAL SMOTHING AND BAYESIAN NETWORK COMBINATION MODELS - Hadi Syafruddin; Ahmadi Ahmadi; Yudha Sukma (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT The dynamics in the development of the security situation are so rapid that there are many political policies that change the security situation of a Country. So that everyone competes to create a technique so that the designed method can be applied especially in the field of security. Indonesia is one of the island states that has an area of sea 2/3 of the land so the source of natural wealth is very abundant, this causes many conflicts of interest with neighboring countries. The number of violations of the Lanal Tarempa region in the Natuna Sea as an example. In the calculation between the degree of violation over time and the application of proper operating patterns it takes a method with a forecasting calculation system (Forcasting) in this case using the Time Series Double Holt Winters Exponential Smothing by combining Holt's (Double Exponential Smoothing) model as a closed system model with the Bayesian Network model as an open system model. This proposed model has the ability to follow a significant pattern of actual data movement. The number of illegal fishing violations based on the data of the last 4 (four) years. The accuracy of an analysis if in the processing of forecasting data results in a small α (Alpha) and β (Beta) value as well as mape, MSE and MAE correction values. KEYWORDS: Security Situation, Breach, Tarempa Naval Base, Operation Pattern, Forecasting and Bayesian Network Model.